2021
DOI: 10.1016/j.bpsgos.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies, Neural Structure, and Depression and Anxiety During the COVID-19 Pandemic: A Longitudinal Study in a Naturalistic Sample Spanning Clinical Diagnoses and Subclinical Symptoms

Abstract: Background Although the COVID-19 pandemic has been shown to worsen anxiety and depression symptoms, we do not understand which behavioral and neural factors may mitigate this impact. To address this gap, we assessed whether adaptive and maladaptive coping strategies affect symptom trajectory during the pandemic. We also examined whether pre-pandemic integrity of brain regions implicated in depression and anxiety affect pandemic symptoms. Methods In a naturalistic sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 53 publications
3
28
2
Order By: Relevance
“…During the COVID-19 pandemic, the use of dysfunctional coping strategies was associated with higher levels of anxiety in the general population (self-blame, venting, behavioural disengagement, and self-distraction) [39] and was also described in patients with psychiatric disorders [40,41]. Bailey Holt-Gosselin and collaborators, using the brief COPE, found that women with more severe anxiety symptoms tended to use more maladaptive coping strategies such as self-distraction, denial, venting, substance use, behavioural disengagement, and self-blame during the COVID-19 pandemic [42]. Poor mental health in general during the pandemic was associated with the use of maladaptive coping strategies such as denial, emotional discharge, or substance use [43].…”
Section: Discussionmentioning
confidence: 97%
“…During the COVID-19 pandemic, the use of dysfunctional coping strategies was associated with higher levels of anxiety in the general population (self-blame, venting, behavioural disengagement, and self-distraction) [39] and was also described in patients with psychiatric disorders [40,41]. Bailey Holt-Gosselin and collaborators, using the brief COPE, found that women with more severe anxiety symptoms tended to use more maladaptive coping strategies such as self-distraction, denial, venting, substance use, behavioural disengagement, and self-blame during the COVID-19 pandemic [42]. Poor mental health in general during the pandemic was associated with the use of maladaptive coping strategies such as denial, emotional discharge, or substance use [43].…”
Section: Discussionmentioning
confidence: 97%
“…The personal characteristics described here constitute antecedents for learning and form the basis of the model to be investigated (see Figure 1 ). They may function as a buffer or as an amplifier for the evaluation and emotional responses to environmental-related strain as experienced in the COVID-19 pandemics ( Dinu et al, 2021 ; Godoy et al, 2021 ; Holt-Gosselin et al, 2021 ).…”
Section: Learning and Performance In Adverse Circumstancesmentioning
confidence: 99%
“…Just as the population in general, university students were affected by affective sequelae of the circumstances during the pandemic, such as excessive feelings of stress or anxiety. Exacerbation of anxiety in the wake of the pandemic was related to usage of maladaptive cognition and coping strategies ( Dinu et al, 2021 ; Godoy et al, 2021 ; Holt-Gosselin et al, 2021 ). These hitherto unknown circumstances of learning posed a threat to wellbeing and mental health which subsequently may have also impacted students’ learning and academic achievement ( Andrews and Wilding, 2004 ; Barch et al, 2019 ; Charbonnier et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to cope adaptively with stressful events is related to the capacity to regulate emotions, which in turn influences the development of anxiety and depression symptoms ( Stanisławski, 2019 ). These symptoms have also been linked with the structural integrity of the brain regions involved in emotion regulation (see Introduction in Holt-Gosselin et al, 2021 ). A recent study used longitudinal data from HCP-DES to investigate whether coping strategies and gray matter content of brain regions involved in emotion assessed pre-pandemic could predict the severity of anxiety and depression symptoms during the pandemic.…”
Section: Recently Published Findingsmentioning
confidence: 99%
“…A recent study used longitudinal data from HCP-DES to investigate whether coping strategies and gray matter content of brain regions involved in emotion assessed pre-pandemic could predict the severity of anxiety and depression symptoms during the pandemic. The authors found that maladaptive coping strategies and lower insula thickness were associated with an increase in anxiety symptoms in patients after the onset of the COVID-19 pandemic ( Holt-Gosselin et al, 2021 ).…”
Section: Recently Published Findingsmentioning
confidence: 99%